ANALYSIS OF THE SUCCESS OF THE MONITORING INFORMATION SYSTEM FOR REGIONAL DEVELOPMENT IMPLEMENTATION (SIMONA) BASED ON THE DELONE & MCLEAN MODEL AND TECHNOLOGY ACCEPTANCE MODEL AT BAPPEDA OF EAST JAVA - Hakim, Arief Rachman; Sukristyanto, Agus; Novaria, Rachmawati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The aim of this research is to examine the influence of information quality, system quality, service quality, on perceived usefulness and perceived ease of use which will then influence behavioral intentions and actual use. The population in this study were all SIMONA users in the East Java Provincial Government. The sample size in this research was determined from 91 regional officials and Bappeda Partners as input supervisors who had used the SIMONA application so that the total research sample was 100 SIMONA application users. The research results show that Information Quality and Service Quality have a significant impact on Perceived Usefulness and Perceived Ease of Use, indicating that users tend to view information and service quality as an important factor in assessing the usefulness and ease of use of a system. On the other hand, System Quality does not show a significant influence on Perceived Usefulness and Perceived Ease of Use, indicating that the technical or functional aspects of the system may not really influence user perceptions of usefulness and ease of use. Furthermore, Service Quality is proven to have a positive effect on Perceived Usefulness and Perceived Ease of Use, indicating that good service can increase user perceptions of usefulness and ease of use. Even though Perceived Usefulness does not have a significant impact on behavioral intentions, Perceived Ease of Use has a positive and significant effect on behavioral intentions, indicating that ease of use has an important role in forming users' intentions to use the system. Finally, behavioral intention was proven to be a significant factor in influencing actual use, indicating that a user's positive intention can predict the actual use of a system.